PROFESSIONAL DEVELOPMENT OF ELEMENTARY SCHOOL TEACHERS THROUGH THEIR WORK AND UNDERSTANDING THE CURRICULUM (TURKEY SAMPLE) - Acar, Esin (European Scientific Journal, ESJ, 2014)
Teacher study groups consist of seminar and course groups are alternative structures for teachers’ professional development. During the practicing of these kinds of study groups, the motivation of participant teachers and the contents of the structures are substantial. The paper explores that the teachers’ perceptions and beliefs about research and inquiry-based learning and the inquiry-based practices during their classroom instructions by trusting their writings and how the activities of teacher study group influence on teachers’ professional development. Additionally, assessing teachers’ answers to the interview questions give an idea about the debates in the professional developments of classroom teachers in Turkey.